Urban growth and land use changes in Tirana, Albania : with cases describing urban land claims - Felstehausen, Herman (Land Tenure Center, University of Wisconsin-Madison, 1999)
Tirana, Albania's capital city, grew rapidly in size and population following 1991 governmental reforms. Before the 1990s, Tirana was a compact city of 225,000 inhabitants. Most properties were state owned. Privatization of land and buildings opened the city to rapid development, heavy traffic, and booming construction of shops, houses, and squatter settlements. Tirana's metropolitan population grew to more than 600,000; city size increased fivefold. This study focuses on land and building claims, both legal and informal, in the context of emerging markets and newly organized land titling and land records systems. A land market action plan supported by the Albanian government, European Union, Land Tenure Center, and others aims to increase tenure security, facilitate property transactions, and strengthen public institutions. So far weak governments and poorly developed institutions still prompt many to invest in property as the only practical means to secure wealth and gain access to improved living. Five urban case studies and one peripheral settlement case are described showing how individuals and families apply a mix of traditional and official means to claim and secure land and building space. Land registration and mapping issues are discussed. Lessons include the role of customary land access and use rules, the need to resolve unclear claims, and the importance of public sector development-particularly infrastructure and government land management. These cases illustrate the difficulty in building public capacity within a private property system. In general within Albania, the public's role is yet to be defined.
iv, 19 p.
Keywords: Land use, Urban Albania Tirana; Land tenure Albania Tirana; City planning Albania Tirana; Land titles Registration and transfer Albania Tirana; Land tenure, Urban Albania Tirana